Los menores de edad en el Ecuador, requieren de un seguro de vida, y asistencia médica, como una obligación adscrita al derecho de alimentos, garantizando su desarrollo integral - Cuenca Cartuche, Rafael Antonio (2011)
The family, to reach its present organization, must have suffered many changes. In the early days, it did not exist, because individuals living in a system of promiscuity, comes after what researchers called matriarchy, that is, clustering of men around the mother, which is easily explained if one considers that motherhood is a fact, true and easy to prove. It appears after patriarchy, in which the family head is the father to finally arrive at the individual family based on marriage monograph. The family founded on marriage, community life, is indispensable, in exchange of consents, the granting each other is done by means of communication, which is a consortium of all life, marriage, not simply a contract that relates to mutual fidelity, but rather the fundamental characteristic is in being part of the family, as the criterion to go to a real and firm, with essence of the natural and true, and that is required by modern law, so the family is a social institution based on marriage, taken to the spouses and children, conservation, propagation and development of the human species in all areas of life, not only marriage but also the affiliation of the law is to ensure adequate mechanisms of social control of the family institution imposing duties and rights. The system of protection of minors and of all bodies, agencies and services that formulate, coordinate, integrate, guide, supervise, evaluate and monitor policies, programs and actions of national public interest and state, for to protect and care for all children and adolescents and to establish the means through which ensure the full enjoyment of rights and guarantees and the performance of the duties prescribed by law, must be subject to the principles of minors. One way to identify the rules by which they must provide the guarantees and rights to minors, and comprehensively, and in the spirit of the doctrine, in integrity to sustain normal growth, it is important to note that the scope and nature of law and the principles which underpin it, say each of the rights recognized by checking the broader implications, and then noted that if one or more rights have been threatened, violated, and even violated, by Therefore it is the duty of the family, and the State to take effective measures relating to cessation of the violation thereof, and restore the enjoyment and exercise of the right violated. To refer to the Rights of the Child, it is important to first consider their personhood, because it is subject to preferential rights, is therefore important to analyze the main rights of persons within its rights regarding minors, to know what guarantees and involve the child and can take place and develop normally in society. The Rights of Children and Adolescents, they are protected from conception to when they have not come of age or eighteen, however, the legislature protects even those who have attained the age of eighteen, this was required by Art . 2 of the Code of Children and Adolescents, which states: Art 2. - Subjects covered. - The rules of this Code apply to every human being from conception until they turn eighteen years old. As an exception, protects persons who have reached that age where expressly provided in this Code.